Barriers to Seeking Mental Health Services among Adolescents in Military Families - Becker, Sara J. (Prof Psychol Res Pr, 2014)
Military families with adolescents experience high levels of stress associated with parental deployment, but many of these families do not seek or utilize mental health services. The current qualitative study was designed to better understand barriers to mental health treatment experienced by adolescents in military families. Focus groups and individual interviews were conducted with military adolescents (n = 13), military (non-enlisted) parents (n = 12), and mental health service providers who treat adolescents in military families (n = 20). Discussions primarily explored barriers to seeking treatment, with supplemental questions assessing the ideal elements of mental health services for this population. Seven barriers to engaging in mental health services were identified: four internal (confidentiality concerns, stigma, ethic of self-reliance, lack of perceived relevance) and three external (time and effort concerns, logistical concerns, financial concerns). Challenges engaging military adolescents in mental health services are discussed and several recommendations are offered for service providers attempting to work with this population.